Atomic mass measurements of neutron-rich nuclides on the path to 78Ni with a β-TOF-equipped MRTOF device - Xian, W.; Rosenbusch, M.; Phong, V. H.; Wada, M.; Schury, P.; Hou, D.; Takamine, A.; Chen, S.; Niwase, T.; Hirayama, Y.; Ishiyama, H.; Iimura, S.; et al. (Frontiers in Physics, 2025)
We report atomic mass measurements of the unstable nuclides 73−75Ni, 73−78Cu, and 74−78Zn, which have been accomplished using multi-reflection time-of-flight mass spectrometry combined with new technical developments to resolve challenges for exotic-isotope identification and selection. The isotopes were produced in-flight at the RIKEN’s Radioactive Ion Beam Facility and delivered to the combined gas cell and multi-reflection system installed downstream of the ZeroDegree spectrometer. The incoming high-energy beam was energy-degraded and subsequently stopped in a helium gas cell. The energy degrader thickness was optimized using a new method that employs signals from plastic scintillators located upstream and downstream of the helium-filled gas cell. Extracted isotopes of interest were mass-selected by the in-MRTOF deflector method, for which we discuss simultaneous selection of multiple isobar chains. The ions of interest were identified unambiguously using β-decay-correlated mass measurements for the first time, which is demonstrated for 78Zn. The new mass values are compared with literature values and recent measurements performed at JYFLTRAP and ISOLTRAP, where a generally good agreement is observed.